Management system proposal for planning and controlling construction waste - Stumpf, M.; Maciel, T.; Kern, A. (Revista Ingeniería de Construcción, 2016)
Construction industry accounts for a significant part of the solid waste generated in urban centers. In part this is due to a lack of culture of reducing the generation or reuse of waste. This sector may improve this situation, seeking to develop management systems. The objective of this paper is to present a proposal for a management system to plan and control construction waste in small and medium sized construction firms. A case study on construction sites was performed in a building company of Novo Hamburgo, Brazil. The planning and control waste system was developed as based on the production system existing in the firm and results point to the feasibility of implementing this system.